2022
DOI: 10.3390/diagnostics12112683
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review on the Multimodal Classification of Depression and Experimental Study on Existing Multimodal Models

Abstract: Depression is a prevalent comorbidity in patients with severe physical disorders, such as cancer, stroke, and coronary diseases. Although it can significantly impact the course of the primary disease, the signs of depression are often underestimated and overlooked. The aim of this paper was to review algorithms for the automatic, uniform, and multimodal classification of signs of depression from human conversations and to evaluate their accuracy. For the scoping review, the PRISMA guidelines for scoping review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Audio and video as well as text may include personally identifiable information that is difficult to eliminate without impairing value of the data. In part for this reason, DAIC-WOZ has been one of the few depression databases made available to qualified researchers [7]. We will seek IRB permission to distribute de-identified and anonymized feature data from this clinical study for use by other researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audio and video as well as text may include personally identifiable information that is difficult to eliminate without impairing value of the data. In part for this reason, DAIC-WOZ has been one of the few depression databases made available to qualified researchers [7]. We will seek IRB permission to distribute de-identified and anonymized feature data from this clinical study for use by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal communication encompasses facial expression, head and body motion, gaze, voice, speech behavior, and speech or language. Yet, as a recent scoping review [7] found, the vast majority of studies on depression include only one or two modalities. This is the case even though large numbers of studies have collected the necessary audio-visual data [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the multimodal approach is common in depression detection, the majority of the existing research focuses on bi-modality or tri-modality. A review study by Arioz et al [35] shows that in the existing 1095 research, only 20 papers devised their methodology on more than two modalities. The prevalent modalities comprise of acoustic characteristics and visual cues, primarily obtained from video recordings.…”
Section: Related Workmentioning
confidence: 99%
“…The approaches discussed suffer from a loss of multimodality due to the absence of feature-merging techniques and reliance on a single classifier for feature mixing. Arroz et al [35] compared algorithms for unimodal, automatic, and multimodal classification conversations, with LSTM and gated recurrent units (GRU). Alternative approaches to multimodal depression detection encompass the examination of various indicators such as the dynamics of acoustic, facial, head movement [27], [39], behavioural and physiological signals [40], brain functional abnormalities, heart rate variability, hemodynamic parameters [41], and partially convergent structural features [23].…”
Section: Related Workmentioning
confidence: 99%